The tides and tidal circulation of Todos os Santos Bay, Northeast Brazil: a general characterization - LESSA,GUILHERME C. (2001)
The Todos os Santos Bay, located on northeastern Brazil, is the second largest coastal bay in the country, after São Marcos Bay. The three main drainage basins convey an average of 120 m³/s of freshwater towards the bay, the majority of it, however, held by a dam in Paraguaçu River since 1985. The original average freshwater inflow was two orders of magnitude smaller than the estimated tidal discharge through the main bay entrance, and the oceanographic characteristics of the bay, as indicated by bay salinity measurements, are clearly marine. The tides are semi-diurnal, and are amplified up the bay by a factor of 1.5. Shallow water constituents become more important as the tide propagates along Paraguaçu Channel and Paraguaçu River, where they generate time asymmetries that change between spring and neap tides. Currents in the bay are mainly bi-directional, and are stronger during the ebbing tide in most of the bay. Offshore, relatively strong tidal currents appear to be felt in a radius of about 10 km, where they are superimposed on winds driven currents orientated to the southwest.